THE RELATIONSHIP OF LANDEK KARO TRADITIONAL DANCE AND THE CHARACTER EDUCATION OF CHILDREN IN SIOSAR VILLAGE KABUPATEN KARO - Fanesa Anastasya Br Depari; Rumiris Lumban Gaol; Ribka Kariani Br Sembiring; Darinda Sofia Tanjung (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This research aimed to assess and determine the relationship of landek karo traditional dance and the character education among children aged 9 to 13 years old in the relocation area of Mount Sinabung, Siosar Village, Pertibi Lama, Kecamatan Merek, Kabupaten Karo, North Sumatra. The population of this research were 156 children aged 9 to 13 years old in Siosar village. The samples were chosen by purposive sampling; in this case the researcher selected 35 children aged 9 to 13 years old. They were the dancers of the Siosar Festival event in September 2019 in Siosar village. This research utilized a quantitative method of survey, which aimed to assess the results of the research by using t-test hypothesis testing. The findings of this research indicated that the average score of tcount for landek karo traditional dance was 24.843 which was greater than ttable namely 1.683 with  high category,  while the average score of tcount for character education was 24.843 which was also greater than ttable namely 1.683 with high category. Therefore, Ho was accepted that there was a relationship between the landek karo traditional dance and the character education of children in Siosar village, Kabupaten Karo.